Critical review of the responsive neurostimulator system for epilepsy - Thomas GP (Dove Medical Press, 2015)
George P Thomas, Barbara C Jobst Dartmouth-Hitchcock Medical Center, Geisel School of Medicine, Dartmouth College, Lebanon, NH, USA Abstract: Patients with medically refractory epilepsy have historically had few effective treatment options. Electrical brain stimulation for seizures has been studied for decades and ongoing technological refinements have made possible the development of an implantable electrical brain stimulator. The NeuroPace responsive neurostimulator was recently approved by the FDA for clinical use and the initial reports are encouraging. This device continually monitors brain activity and delivers an electric stimulus when abnormal activity is detected. Early reports of efficacy suggest that the device is well tolerated and offers a reduction in seizure frequency by approximately half at 2 years. Keywords: medically refractory epilepsy, seizures, brain surgery, brain stimulation, neurostimulation